First Year Real Life Experience With Intravitreal Brolucizumab for Treatment of Refractory Neovascular Age-Related Macular Degeneration - Abdin, Alaa Din; Aljundi, Wissam; El Jawhari, Khalil; Suffo, Shady; Weinstein, Isabel; Seitz, Berthold (Frontiers in Pharmacology, 2022)
Purpose: To assess the morphological and functional outcomes within the first year of treatment with intravitreal brolucizumab for refractory neovascular age-related macular degeneration (nAMD). Methods: This retrospective study included 21 eyes from 19 patients with refractory nAMD followed for 12 months. All patients were switched to brolucizumab after treatment with at least two other anti-vascular endothelial growth factors (VEGF). All eyes received 3x brolucizumab 6 mg/0.05 ml intravitreal injections (IVI) monthly as an upload phase. Then eyes received an IVI every 8 weeks with interval adjustment to every 12 weeks if disease activity was not present. Main outcome measures: best corrected visual acuity (BCVA), central macular thickness (CMT) and retinal fluid distribution. In addition, we reported the adverse event rate. Results: The number of previous anti-VEGF IVIs/eye was 36 ± 22 before switching to brolucizumab. BCVA (ETDRS) was 51 ± 16 before treatment and 50 ± 19 at week 52 (p = 0.6). CMT was 374 ± 158 μm before treatment and 298 ± 92 μm at week 52 (p = 0.01). The number of IVIs/eye decreased from 9.6 ± 1.9 IVIs in the last year before switching to 6.4 ± 0.9 IVIs in the first year after switching to brolucizumab (p < 0.001). The rate of eyes with subretinal fluid and pigment epithelial detachment decreased at week 52. Finally, two cases of intraocular inflammation were observed as adverse events. Conclusion: In the first year of treatment, intravitreal brolucizumab was able to stabilize visual acuity with significantly less IVIs in patients with refractory nAMD. It also improved anatomic outcomes in these patients, particularly reducing subretinal fluid and pigment epithelial detachment and subsequently central macular thickness. However, two cases of intraocular inflammation were observed as adverse events.